Encouraging the electrification of road transport at the regional level by creating an appropriately designed logistics centre - Schein, Péter; Skapinyecz, Róbert (Advanced Logistic Systems - Theory and Practice, 2024)
The purpose of this paper is to examine how the more intensive electrification of urban and regional freight transport could be promoted with the help of a logistics centre to be created specifically for this purpose. Electrification requires more and more attention to make the transport of goods sustainable and to reduce harmful emissions. Besides, the advantages of electric freight transport can be, for example, the lighter regulations for electric cars and the tender resources that can be used for their purchase. However, while the technological capabilities of electric road freight transport vehicles are rapidly evolving careful infrastructural planning and expansion are still required to aid their wider adoption. For electric goods transport to be realized in an efficient way, the location of a possible logistics centre in the examined region – the city of Miskolc and its surroundings – is presented, based on the analysis of the local infrastructural conditions.